Science Teaching Materials Based on Field Trips with Local Wisdom to Improve Elementary School Students' Critical Thinking - Ajeng Raja Azura; Suryanti Suryanti; Eko Hariyono (International Journal of Current Educational Research, 2023)
Objective: Education is the most essential thing in the life of a human being. Components supporting its implementation are needed to realize the quality of education. Cultivating critical thinking character education is urgently required in the era of globalization. Field trip teaching materials with local wisdom can be an attractive alternative. This study aims to develop science teaching materials based on field trips with local wisdom to improve elementary school students in critical thinking skills. Method: This research method uses research and development, Borg and Gall. Data collection techniques used unstructured interviews, observation, assessment tests, and non-tes. At the same time, data analysis uses quantitative data and descriptive elaboration. Results: The study showed the validity of teaching materials in this research with a percentage gain of 82.00% if converted to a valid category. In comparison, the practicality of implementing lesson plans obtained a percentage of 94.00%, and student activity obtained a percentage of 95.00% with an outstanding category. The effectiveness of science teaching materials showed pretest results with an average of 66.30, while the post-test data was 87.22. Novelty: This research shows a significant increase in the critical thinking skills of elementary school students through learning science teaching materials based on field trips with local wisdom. The update of this research is to implement field trip activities into teaching materials so that learning in cultivating critical thinking is exciting for students.